ANALYSIS OF Cr, Cu, and Zn CONCENTRATIONS IN THE SHELLS (Meretrix meretrix) FROM PANTAI CERMIN OF SERDANG BEDAGAI REGENCY, NORTH SUMATRA PROVINCE - Della Afriyola; Bintal Amin; Yusni Ikhwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in March 2018 by taking samples of Meretrix meretrixfrom Pantai Cermin of Serdang Bedagai Regency, North Sumatra Province.The purpose of this research was to determine the metal concentrationsof Cr, Cu and Zn in the shells based on the size from different stations, to evaluate the differences in metal concentrations between umbo and periostacum,as well as to find out the level of metal pollution based on MPI (Metal Pollution Index). Analysis of metal concentrations of heavy metal was done byPerkin Elmer 3110 Atomic Absorption Spectroscopy (AAS). The results showed that the highest Cr metal concentration in umbo was found at Station 3 (10,253 µg/g) in large sizes, the highest Cu was at Station 2 in large size (4,173 µg/g) and for Zn was found at station 2 (132,867 µg/g)in large size. Mean while the highest concentration of Cr in Periostacum was at Station 3 (7,320 µg/g)in large size, Cu was at Station 2 (3,747 µg/g) in small size, and for the highest Zn was at Station 2 (98,777 µg/g)in small size. The concentration of Cr, Cu and Zn was higher in the umbo than periostacum. Based on this study, the MPI value of Pantai Cermin was 10,36 which was quite comparable to other studies. Keywords: Pollution, Heavy Metal,Meretrix meretrix, Pantai Cermin